PWE-433 A qualitative assessment of cognitive framework development in novice endoscopists: implications for programmed lesion recognition training. (22nd June 2015) - Axe, K; Hawkes, E; Turner, J; Hurley, J; Neville, P; Warren, N; Hawkes, N
Abstract : Introduction: UK training pathways in upper GI endoscopy (UGIE) constitute a mandatory JAG Hands-on Course and supervised endoscopy experience. Trainee surveys have highlighted a deficit in formal endoscopic lesion recognition (ELR) training. We aimed to evaluate a range of teaching formats for ELR for novice UGIE trainees, determining key elements in development of their cognitive framework (CF). Method: As part of a Structured Programme of Induction and Training in UGIE (SPRINT) we delivered ELR teaching sessions at months 0, 1, 2 and 4 in different formats – small group discussion (still image); small group (video); online Standardised Lesion Assessment Tests in Endoscopy (SLATE); and one-to-one training at hands-on sessions. All 7 trainees evaluated sessions at time of delivery. A semi-structured interview was conducted at month 4 (40 mins) exploring the relationship of training to development of ELR skills. A deductive approach to data analysis using a modified grounded theory approach 1 was followed. Results: ELR sessions were highly valued, both for content and relevance to training. Formative assessment established baseline declarative knowledge, but learners expressed anxieties related to exposing lack of knowledge. At baseline, small group sessions (supportive, non-threatening) involving all trainees, using common pathologies, correcting misconceptions and exploring differential diagnoses, were highly valued and supported learning. Online testing of this subject matter in the first 3 months provided useful reinforcement, if allied to detailed feedback. Teaching classification systems aids higher level CF development, if illustrated with numerous examples in various contexts. After 3 months, management plans and report writing (meta-cognitive skills) need emphasis, with testing of procedural knowledge recall. Video cases, rare presentations of common disease and rare pathologies are only usefully integrated into mental frameworks at or after 4 months. Interactive Q&A group formats remained highly valued at this stage. SLATE assessment charted progress, but lacked immediate, targeted feedback and created performance-related focus on marks. Conclusion: Delivery and format of ELR training must be matched to CF development. Initial exposure should focus on common pathologies, to develop confidence and observation skills. Once handling skills are secure, structured observation and classification structures link knowledge at a deeper level. Formative assessment, feedback and discussion drive learning. Disclosure of interest: None Declared. Reference: Burnard P, et al . Br Dental J. 2008;204:429–432